Synergystic Role of Cocopeat Matrix and Foliar Nutrient Type on Aclimatization Success of Micropropagated Dendrobium Seedlings - Baharuddin Mohammad Luthfi; Ramdan Hidayat; Pangesti Nugrahani (Universitas Labuhanbatu, 2025)
Background: Dendrobium orchids have high economic value (in 2020 generated an export value of US61.87 thousand), yet micropropagated seedlings commonly exhibit slow growth and high mortality during the acclimatization stage. This problem is largely associated with the use of unsuitable planting media and inadequate nutrient supply, which limit seedling adaptation and survival after tissue culture. This study aims to determine the best combination of planting media and foliar fertilizer types for the growth of Dendrobium orchid seedlings during the acclimatization stage. Methodology: The study was conducted in Penambangan Village, Semanding District, Tuban Regency, East Java Province from November 2024 to February 2025 using a Completely Randomized Design (CRD) with 9 treatment combinations and 4 replications. The first factor was the treatment of planting media types (M1: Black Moss, M2: Rice Husk Charcoal, M3: Cocopeat), and the second factor was the type of foliar fertilizer (P1: Gandasil D, P2: Gaviota 63, P3: Grow Quick LB). The observed research variables included the percentage of live seedlings, plant height, leaf area, seedling growth rate, number of shoots, and number of roots. Findings: The results showed that the use of cocopeat planting media resulted in the highest percentage of seedling survival at 88.33%. The combination of cocopeat planting media and Grow Quick LB leaf fertilizer produced the best relative growth rate (RGR) at 8-12 WAP of 41.22 mg/month.This research produces the best combination of planting media and foliar fertilizer for orchid seedlings at the acclimatization stage. Contribution: The findings contribute to a more systematic understanding of how substrate physical properties and foliar nutrient supply interact to influence survival and growth performance during orchid acclimatization, offering a scientifically grounded framework for improving ex vitro propagation efficiency